Manajemen Pendidikan Islam Dalam Keluarga - Murtopo, Bahrun Ali (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2016)
AbstrakIndividualâs relationship in a family environment very affects childâs psychological and the impact will be seen when she is a teenager. Loving atmosphere and conducive atmosphere in an intellectual development which have been built in a family will make a child able to adapt himself, with his family and the surrounding community. Many experts proved that children who grew up in a home without parental supervision more have problem than children who receive supervision from their parents.Therefore, the formation of a family required an integrated education program and directed education program. Education programs in this family must be able to give a clear job description for each individual in the family, so that each individual can perform an ongoing role for the creation of a conducive family environment to educate children maximally.In the first part of this book we will describe some of the significant factors in outlines family education according to the Islamic teaching, which is as follows.Keywoard: konsep keluarga Islami, Hak dan kewajiban, Implikasiss